The socio-economic impact of regional shopping centres on surrounding retail distribution with particular reference to the Somerset Mall, Somerset West - Waring, Lauren A (Stellenbosch : Stellenbosch University, 2012)
Study project (M. of Town and Regional Planning) -- University of Stellenbosch, 1994.